2017
DOI: 10.1371/journal.pone.0168439
|View full text |Cite
|
Sign up to set email alerts
|

Adult Tea Green Leafhoppers, Empoasca onukii (Matsuda), Change Behaviors under Varying Light Conditions

Abstract: Insect behaviors are often influenced by light conditions including photoperiod, light intensity, and wavelength. Understanding pest insect responses to changing light conditions may help with developing alternative strategies for pest control. Little is known about the behavioral responses of leafhoppers (Hemiptera: Cicadellidae) to light conditions. The behavior of the tea green leafhopper, Empoasca onukii Matsuda, was examined when exposed to different light photoperiods or wavelengths. Observations include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Lights at night tended to suppress the activities of leafhoppers including moving, cleaning and, most importantly, mating activities, which maybe contributed to a decrease in the population size of E. onukii in tea plantations [ 42 ]. Previous studies have reported that under controlled conditions, light can change the behaviors of E. onukii, including its circadian rhythm [ 42 ]. The consequence of this behavioral change may include unsynchronized mating activities between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Lights at night tended to suppress the activities of leafhoppers including moving, cleaning and, most importantly, mating activities, which maybe contributed to a decrease in the population size of E. onukii in tea plantations [ 42 ]. Previous studies have reported that under controlled conditions, light can change the behaviors of E. onukii, including its circadian rhythm [ 42 ]. The consequence of this behavioral change may include unsynchronized mating activities between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…In 1972, the mosquito Anopheles gambiae Giles was found to exhibit a burst of flight activity upon exposure to artificial light (even at low intensities of 0.3 lux) instead of the flight inhibition expected in nocturnal species (Jones et al., ). In contrast, light at night (especially green wavelengths) suppresses locomotor and cleaning activity in the tea green leafhopper, Empoasca onukii Matsuda (Shi et al., ). These modifications of locomotor activity may be associated with alterations of feeding behavior.…”
Section: Life History and Behavioral Responses To Alan And Their Undementioning
confidence: 99%
“…The escape reaction in response to illumination that exceeds a certain intensity threshold can be a manifestation of stress in an animal, which is suddenly exposed to dramatic sensory overstimulation. However, despite extensive observations of behaviors associated with overstimulation of the visual system in P. americana and similar nocturnal insect species (Godden and Goldsmith 1972;Shi et al 2017;Shimoda and Honda 2013), questions remain about relative contributions of different visual channels to visual overstimulation-induced reactions, and to specific behavioral reactions associated with stress. Grooming, a complex, often stereotypic process of cleaning body surfaces and sensory appendages, which has been extensively studied in both vertebrates and insects (for review see (Hlavac 1975;Smith and Valentine 1985)), is one such behavior that changes in stressed animals (Kalueff et al 2016;Tinbergen 1951;Zhukovskaya et al 2013).…”
Section: Introductionmentioning
confidence: 99%